Influence of convection on the formation of adsorbed film surfactants under dynamic changes in the surface area of solution - Mizev Аleksey Ivanovich; Bratsun Dmitriy Аnatolievich; Shmyrova Аnastasia Ivanovna (Computational Continuum Mechanics, 2016)
The dynamics of surface phase formation in the aqueous solutions of surface-active substances (surfactants) during one compression-expansion cycle in the Langmuir trough was investigated both experimentally and theoretically. The organic salts of fatty acids such as potassium laurate, caprylate and acetate, being members of a homologous series, were used as surfactants. The results of our experiments indicate that the plot of the surface pressure increment observed under maximum surface compression against the volume concentration has a maximum, the position of which differs for all tested surfactants. It is shown that the maximum position coincides with the concentration value at which the saturated monolayer of surfactant molecules is formed on the free surface. A theoretical model that takes into account the effect of forced convection in the bulk of solution originated from the barriers motion is proposed to interpret the experimental results. This model allows us to reveal the main kinetic characteristics of adsorption/desorption processes of the investigated substances. The model describes well the laboratory results, but there is a discrepancy between theory and experiment when diffusion is considered as the only mechanism of transfer of surfactant molecules in the volume. A new method for measuring the Langmuir-Shishkovsky constant was developed.